Study of Structural and Functional Defects In Choledochal Cyst (Journal of Chittagong Medical College Teachers' Association, 2014)
Although many research works have been undertaken over decades to find out the etiology and mechanism of the structural defects resulting in formation of choledochal cyst and the consequent physiological dysfunction, the exact cause remained obscure. This study was undertaken to explore what structural changes in the choledochal cyst leads to its dilatation, at the same time it was also decided to find out how the choledochal cyst behaves with volume change. The study was conducted on 10 children with choledochal cyst in the Department of Paediatric Surgery, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka during the period of March 2007 to October 2008 by infusing a volume of contrast diluted with normal saline with the help of peroperative cholangiogram and a pressure measuring device. Biopsy was taken from resected choledochal cyst wall and wall of the CBD unaffected by the cyst. We hypothesized that, choledochal cyst is plastic in nature and there is increase of collagen fibers than elastic fibers in the wall of choledochal cyst that causes its dilatation. Out of 10 patient 2 were male and 8 were female. In quantitative estimation of collagen and elastic fiber, in control quantity of collagen fiber mean 106.40 ± 49.50, quantity of elastic fiber mean 79.80 ± 15.98, proportion of collagen and elastic fiber mean 1.35 ± 0.59 and in case (from choledochal cyst wall) quantity of collagen fiber mean 199.60 ± quantity of elastic fiber mean 46.10 ± 1.50, proportion of collagen and elastic fiber mean 4.76 ± 1.96. All this findings are statistically significant (p. value < 0.001). From the study it concluded that, choledochol cyst is plastic in nature showing almost a sigmoid shaped curve and increase in the collagen fiber over the elastic fiber in its wall causing dilatation with resultant stasis.JCMCTA 2014 ; 25 (2) : 46-48